Reciprocal Interactions Between Regulatory T Cells and Intestinal Epithelial Cells - Jiang, Zhiqiang; Wu, Chuan (Frontiers in Immunology, 2022)
It has been well established that Foxp3+ regulatory T cells (Treg cells) play a crucial role for immune repression and tolerance, protecting the body from autoimmunity and inflammation. Previous studies indicate that intestinal Treg cells are one specialized population of Treg cells, distinct from those in other organ compartments, both functionally and phenotypically. Specific external and internal signals, particularly the presence of microbiota, shape these Treg cells to better cooperate with the gut ecosystem, controlling intestinal physiology. The integrity of intestinal epithelial barrier represents a key feature of gut immune tolerance, which can be regulated by multiple factors. Emerging evidence suggests that bidirectional interactions between gut epithelium and resident T cells significantly contribute to intestinal barrier function. Understanding how Treg cells regulate intestinal barrier integrity provides insights into immune tolerance-mediated mucosal homeostasis, which can further illuminate potential therapeutic strategies for treating inflammatory bowel disease and colon cancer.